Overhead crane control upgraded to variable frequency drive and wireless remote controller for programming logic circuit - Omar, Muhamad Nazri (2024)
Radio Frequency (RF) remote controllers are widely used in manufacturing, construction, transportation, and many other industrial applications. Cranes, drills, and miners, among others, are commonly equipped with Radio Frequency (RF) remotes. In this thesis focused on overhead crane in steel manufacturing industry. Installation wired communication takes a long time to set up the connection as compared to the wireless connection. The installation becomes very lengthy and complex to get connected with each router. In future to connect one more device with the network, then it must do the setup again. However, in the wireless connection, don’t have to perform all the setup again. Only must access the network with the authorized passcode. Radio-controlled devices are ubiquitous in all sorts of industries. In fact, many cranes are now being equipped with radio-controlled technology, which is revolutionizing the way crews move materials around a warehouse or job site. On the same time, in steel manufacturing industry is still used old technology which is the motor starter of existing cranes is using Rotor Resistance Starter with AC Slip Ring motor type which are need to be improve to Inverter or Variable Frequency Drive (VFD) in this thesis presented. Most of the industries nowadays are using VFD or Inverter with their electrical equipment such as overhead crane as for purpose is Energy Saving, High Operational Efficiency, easy for Maintenance and easy to link with advance technology application such as Programming Logic Circuit (PLC). The study's few main goals are to investigate the overhead crane performance based on Steel Manufacturing Overhead Crane failure and downtime, upgraded motor starter from Rotor Resistance Starter to Variable Frequency Drive (VFD) with Slip Ring AC motor type and design new Remote Controller with wireless communication system including Transmitter (Tx) and Receiver (Rx). The research was divided into three parts. First, is to design new Remote Controller with Wireless Communication System based on Transmitter (Tx) and Receiver (Rx) communication in order to replace existing controller which is Pendant and Joystick Controller which to improve the demand of more manpower (operator to conduct crane activity), enhance safety and simplify the wiring design. Second is to investigate the overhead crane performance of base on previous of motor starter design which is Rotor Resistance Starter before implement new motor starter which is Variable Frequency Drive (VFD). Third is to upgrade motor starter from Rotor Resistance Starter to Variable Frequency Drive (VFD) in order to improve motor start up, hoisting anti-sway for safety concern and cost saving for purchase maintenance spare part in in steel manufacturing industry. Through the surveillance and monitoring of wireless remote control motor starter control for crane that done at Ann Joo Steel (AJSB), Prai, Penang, Malaysia. The findings and analysis on the application of wireless remote controllers and variable frequency drives (VFDs) to overhead cranes in the steel manufacturing sector. Following that, a methodology for estimating system upgrading of the overhead crane in the steel manufacturing industry is established by utilising the transmitter (Tx) and receiver (Rx) with a new complete set of Variable Frequency Drive (VFD). The suggested system estimation method's applicability is demonstrated through case studies. The design of the new control system wire is divided into three components, each based on the current design of the old control wiring.